1994
DOI: 10.1007/bf00166159
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of murine ?1-proteinase inhibitors: Gene amplification and reactive center divergence

Abstract: The organization and sequence of genes encoding the alpha 1-proteinase inhibitor (alpha 1PI), a major serine proteinase inhibitor of the mammalian bloodstream, have been compared in several species, including murine rodents (genus Mus). Analysis of gene copy number indicates that amplification of alpha 1PI genes occurred at some time during evolution of the Mus genus, leading to fixation of a family of about three to five genes in several existing species (e.g., M. domesticus and M. saxicola), and only a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…We have expressed the serpin-1 variants as recombinant proteins and found proteinase inhibitor activity for 11 of the 12 reactive sites. 3 The individual variants can inhibit enzymes with chymotrypsin-, elastase-, or trypsin-like specificities. Serpins in insect hemolymph might inhibit proteinases produced by pathogenic microorganisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have expressed the serpin-1 variants as recombinant proteins and found proteinase inhibitor activity for 11 of the 12 reactive sites. 3 The individual variants can inhibit enzymes with chymotrypsin-, elastase-, or trypsin-like specificities. Serpins in insect hemolymph might inhibit proteinases produced by pathogenic microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons of serpin sequences have demonstrated that the reactive site loop and adjacent sequence is the least conserved region of the proteins. It has been suggested that after duplications of serpin genes, rapid evolutionary change of the reactive site loop region provides new inhibitor selectivities that may have value during natural selection (2,3).…”
mentioning
confidence: 99%
“…5) overlap by approximately 1 kb. Thus, well-characterized molecular clones containing the two for target proteinases-is hypervariable, and it has evolved much more rapidly than other parts of the proserpin gene subclusters, as well as the entire region between them, are now available; these should be use-tein (Hill and Hastie, 1987;Inglis and Hill, 1991;Rheaume et al, 1994). ful for functional studies of the region.…”
Section: Figmentioning
confidence: 98%
“…Krauter, 1991;Goodwin et al, 1996). Similarly, there One approach to studying the evolution of the serpin is 1 AACT gene in the human genome, whereas its superfamily has been to compare the primary se-murine counterpart, the Spi-2 locus, comprises 10 quences (Hill and Hastie, 1987; Borriello and Krauter, tightly linked genes in 129/St mice (Inglis and Hill, 1991;Inglis and Hill, 1991;Rheaume et al, 1994;Good-1991).…”
Section: Figmentioning
confidence: 98%
See 1 more Smart Citation